The Influence of Budget Objective Characteristics and Decentralization Structure on the Performance of the Merangin Regency Youth and Sports Tourism Office - Windi Afriani Azhari; Iskandar Sam; Salman Jumali (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to determine the influence of budgetary goal characteristics and decentralization structure on the performance of the Regional Device Organization Disparpora of Merangin Regency. The sample in this study is the Health Company using the probability sampling technique, resulting in 35 trial samples and 50 respondents for the research sample. The analysis methods used in this research are classical assumption tests, multiple linear regression analysis, and hypothesis testing with the aid of SPSS V 27 For Windows software. The method of data collection was through documentation and literature study. The research results conclude that the characteristics of the budget and the structure of decentralization together have a significant impact on the performance of the regional device organization of the Department of Tourism, Youth, and Sports of Merangin Regency.